0344 Use of an Adjustable Bed Base Improves Sleep Quality and Duration. (25th May 2022) - Danoff-Burg, Sharon; Rus, Holly; Burke, Colin; Weaver, Morgan; Rodriguez, Rodolfo; Carmon, Kiara; Ledesma, Duvia Lara; Gottlieb, Elie
Abstract: Introduction: The positional adjustment of a bed can potentially contribute to better sleep and alleviation of discomfort associated with a variety of medical conditions. As most studies in this area have focused on inclined sleeping for therapeutic purposes, understanding the impact of postural change on improving sleep among healthy individuals requires further research. This study compared sleep in an inclined position on an adjustable bed base to participants' prior sleep on their original bed bases. Methods: Healthy adults (61% female, ages 23-60) willing to sleep at an incline participated in an 8-week field study, using a pre-post intervention design. During the 4-week baseline period, participants used their regular bed base at home. During the 4-week intervention period, they used the Mattress Firm 600 Adjustable Base at home with head and/or feet raised (not flat). Sleep was measured objectively using SleepScore Max every night and by daily and pre-post self-report. Multilevel regression and paired t-tests were used to test for statistical significance. Results: There were over 1, 100 nights of tracked sleep across 26 participants. Objective sleep measurements showed many nightly improvements during the intervention compared to baseline: increased time in bed (+21 minutes, p=.003), total sleep time (+21 minutes, p=.001), and REM (+5 minutes, p=.009); less WASO, both in duration (-3 minutes, p=.046) and proportion of the night (p=.015); fewer awakenings (p=.034); and better sleep maintenance (p=.014). Improvements also were observed in 3 objective sleep quality measures: SleepScore, BodyScore, and MindScore (ps<.05).Self-report measures revealed greater comfort and enjoyment when using the adjustable base, as well as perceived improvement in a variety of outcomes, including time to fall asleep and falling asleep within a preferred amount of time, ability to sleep through the night, sleep duration, sleep quality and satisfaction, and feeling more rested in the morning (ps<.05). Conclusion: Objectively-measured sleep and self-reported sleep improved in duration and quality when using the adjustable base compared to healthy adults' original bed bases. Furthermore, qualitative and quantitative self-report results suggested that the intervention was perceived as a comfortable and enjoyable experience. Support (If Any): Mattress Firm INC